Factors influencing of tourist loyalty: a study on tourist destinations in Malaysia - Haque, A. K. M. Ahasanul; Khan, A (2013)
This study was trying to explore factors that lead to tourist’s loyalty inn terms of choice tourist destinations .This research was conducted three stages of data analysis for instance: descriptive statistics, exploratory factor analysis; and multiple regression analysis to test the hypothesis. Multiple Regressions was employed to identify the relationship among the variables. Results showed that Destination Image, Perceived Value and Service Quality have a positive relationship with tourist loyalty on tourist destination in Malaysia. Explore of significant factors influencing tourist satisfaction for making strategic marketing plans to encourage tourists to visit in Malaysia. Incompletion, the outcome of this study provides a useful source of information for global marketers to understand and satisfaction, finally positive loyalty towards tourism destination in Malaysia